2021
DOI: 10.4309/jgi.2021.48.2
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study in Gambling Recovery Communities: A Comparison Between ‘‘Pure’’ and Substance-Abusing Gamblers

Abstract: Most of the available literature has shown that gambling disorder (GD) is often associated with several psychiatric conditions. Comorbidities with mood disorders, impulsiveness, personality traits, and impairments in cognitive function have also been frequently investigated. However, it is currently uncommon to study this disorder in individuals without comorbid substance abuse; therefore, the primary aim of our study was to compare the psychological profile of individuals with GD with and without substance us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…Therefore, the purpose of the present study is to extend the findings of a previous study of ours [54], in which it was found that the "pure" GD group differed from the SDG group primarily in terms of mood disorder traits such as depression, anxiety, and hostility. To this end, different emotional and affective dimensions have been included, along with the creation of an affective task, with the aim of shedding light on both the emotional aspects and their impact on risk-taking decision-making processes.…”
Section: The Present Studysupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, the purpose of the present study is to extend the findings of a previous study of ours [54], in which it was found that the "pure" GD group differed from the SDG group primarily in terms of mood disorder traits such as depression, anxiety, and hostility. To this end, different emotional and affective dimensions have been included, along with the creation of an affective task, with the aim of shedding light on both the emotional aspects and their impact on risk-taking decision-making processes.…”
Section: The Present Studysupporting
confidence: 56%
“…This is because the use of other substances can be confusing in attributing factors that play a role in gambling behaviour. Previous studies have highlighted neurobiological alterations that appear to be independent of substance intake [68] and have shown the presence of exclusive factors (e.g., Gambling Disorder severity, mood disorder) in a sample of "pure" gamblers in-treatment [54]. The lack of adaptive emotion regulation strategies appears to modulate the relationship between personality traits and gambling severity, in which gambling may represent a way to suppress negative affective states and escape personal needs (i.e., gambling as a coping strategy) [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young [ 35 ] was the first to outline specific diagnostic criteria for IA, based on the DSM-IV diagnostic criteria [ 36 ] for pathological gambling, with which IA shares symptomatic overlap; drawing on this criteria, she constructed a diagnostic questionnaire (i.e., Young’s Internet Addiction Test; IAT) [ 35 ]. Research using the IAT has shown that IA has characteristics and symptoms comparable to those of gambling disorder (e.g., preoccupation, tolerance, withdrawal, failure to control, impaired decision making) and comorbidity with depression and anxiety [ 37 , 38 , 39 ], obsessive-compulsive symptoms [ 40 , 41 , 42 , 43 ], attention deficit and hyperactivity disorder [ 44 ], and hostility–aggression behaviors [ 45 , 46 ]. Nevertheless, IA is not classified as a specific psychiatric disorder, but a psychological symptom that may arise in various psychopathological frameworks.…”
Section: Introductionmentioning
confidence: 99%